A three‐factor model of educational practice considerations for teaching neurodiverse learners from a strengths‐based perspective. Issue 4 (21st October 2021) - Sewell, Alexandra; Park, Jane
Abstract : The purpose of this practice paper is to promote the teaching of learners with neurodevelopmental conditions from a neurodiverse perspective. The challenge teachers face in having to draw on up‐to‐date research evidence and theoretical perspectives, and align these with practical considerations to generate contextualised teaching strategies, are addressed with the introduction of a three‐factor model. The utility of considering pupil assessment data gathered from a strengths‐based perspective is positioned as a central component to bridging the gap between the incipient neurodiversity literature and the realities of applied teaching practice. Two case examples have presented that draw on the proposed three‐factor model to demonstrate how teachers can assess and teach learners from a neurodevelopmental perspective. These case studies focus on supporting learners with Autism and Attention Deficit Hyperactivity Disorder in a secondary setting.